Reduction of enzymatic browning of harvested 'Daw' longan exocarp by sodium chlorite - Khunpon B. (2014)
Post-harvest exocarp browning is a major problem resulting in reduced shelf-life of longan fruits. The objective of this study was to evaluate the possibility of using sodium chlorite (SC) as an anti-browning agent for controlling enzymatic browning of harvested longan fruits during storage at ambient conditions. Longan fruits cv. Daw were dipped in 0.001%, 0.005%, 0.01%, and 0.05% SC (W/V) for 10 min. The fruits were packed in cardboard boxes and stored at 25±1 °C with a relative humidity of 82±5% for 72 h. Changes in browning index, colour parameter (L* and b* values), polyphenol oxidase (PPO) activity, peroxidase (POD) activity, and total phenolic content were measured. The results showed that the fruits treated with SC had lower browning index, but higher L* (lightness) and b*(yellowness) values than those of the control group during storage for 48 h. SC at a concentration of 0.01% was the most effective in reducing exocarp browning. The application of SC reduced PPO and POD activities and delayed a decrease in the total phenolic content. The treatment with 0.01% and 0.05% SC had the lowest PPO and POD activities, and maintained the highest total phenolic content. It was concluded that an application of SC is an alternative method for reducing exocarp browning and maintaining quality of harvested longan fruits.